Tipos e tipologias de estruturas escolares - Quintas, Kamily Victoria de Barros (Brasil, 2025)
The research discusses the school space linked to the processes of democratization established in Brazil. In this way, it addresses the types and typologies of schools in the urban public network of Manaus used to meet the demand for basic education. The project is part of a series of other ongoing studies that analyze the challenges of democratizing education, its connection to school spaces, and the need for new pedagogical and educational tools for an education of the future. Therefore, based on documentary collection from the competent agents within the secretariats, we categorized the typologies with forms and structures of existing school buildings in the network, as part of the democratizing processes of education and learning in a present-day school, which often seeks, with spaces and tools from the past, an education for the future.